1985
DOI: 10.1021/bi00344a053
|View full text |Cite
|
Sign up to set email alerts
|

Methyl-esterified proteins in a mammalian cell line

Abstract: Methyl esterification of carboxylic acid residues in intact mouse S49 lymphoma cells was examined, and at least 24 proteins were found to be modified. Cell fractionation revealed that a distinct set of these proteins could be found in each of the four fractions. Nuclei contained 11 methyl-esterified proteins at 12, 15.5, 18, 19, 39, 41, 45, 70, 90, 105, and 130 kilodaltons (kDa). Five proteins copurified with the plasma membrane/mitochondrial fraction at 13, 24, 25, 27, and 28 kDa. Two proteins at 32 and 56 kD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 35 publications
(39 reference statements)
2
14
0
1
Order By: Relevance
“…Our results are in accordance with the previous findings showing that carboxymethylation of prenylated Rho peptide and catalytic subunits of PDE6 significantly increases their affinity for RhoGDI and PDEδ, respectively (33,36). Carboxymethylation is the only step in the posttranslational modification of the CaaX motif that is potentially reversible (37). The importance of the methyl group in KRAS4b binding to PDEδ highlights the potential regulatory significance of this modification in trafficking KRAS4b to cellular membranes.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in accordance with the previous findings showing that carboxymethylation of prenylated Rho peptide and catalytic subunits of PDE6 significantly increases their affinity for RhoGDI and PDEδ, respectively (33,36). Carboxymethylation is the only step in the posttranslational modification of the CaaX motif that is potentially reversible (37). The importance of the methyl group in KRAS4b binding to PDEδ highlights the potential regulatory significance of this modification in trafficking KRAS4b to cellular membranes.…”
Section: Discussionsupporting
confidence: 93%
“…This hypothesis is consistent with in vitro liposome binding data that revealed that whereas methyl esterification of the a carboxyl group of a prenylated CAAX peptide affords only minimal added binding affinity when a geranylgeranyl modification is used, the increase is 20-fold for a farnesyl modification (25). Because carboxyl methylation is reversible under physiologic conditions (11), this modification may specifically regulate the affinity of farnesylated proteins for membranes. These observations suggest a reason for the evolution of two alternative forms of protein prenylation: farnesylation is a modification for proteins that require a relatively low and reversible affinity for membranes, whereas geranylgeranylation is for pro- [Modified from ref.…”
Section: Role Of Postprenylation Processingsupporting
confidence: 85%
“…Finally, the newly C-terminal prenylcysteine becomes a substrate for a specific protein carboxyl methyltransferase, Icmt, that methyl esterifies the a carboxyl group of the prenylcysteine (5, 9, 10). Unlike prenylation and proteolysis, carboxyl methylation is reversible under physiologic conditions (11), although a specific esterase that hydrolyzes the prenylcysteine methyl ester has not been identified. When a CAAX sequence ends in an amino acid other than leucine or phenylalanine (typically serine, methionine, or glutamine), it is modified with a 15 carbon farnesyl isoprenoid through the activity of FTase, whereas when the terminal amino acid is leucine or, in some cases, phenylalanine, the modification is with a 20 carbon geranylgeranyl isoprenoid through the action of GGTase (12).…”
Section: Caax Processingmentioning
confidence: 99%
“…Furthermore, data from excised patches indicate that the methylation reaction affects the channel open probability, even though a small effect on channel density cannot be completely ruled out (since the P o after DZA treatment is so low that the number of sodium channels per patch cannot be accurately determined). Since, in the absence of AdoMet, channel activity in excised patches is generally unstable, the methylation reaction in A6 cells is probably easily reversible, in keeping with the reversibility of methylation of other membrane proteins (48,53,54). In addition, for ENaC expressed in lipid bilayers, methylation is capable of activating sodium channels (30).…”
Section: Adomet Plus Gtp Increases the Open Probability Of Sodium Chamentioning
confidence: 99%